Analysis on the Stability of In-Surface Magnetic Configurations in Toroidal Nanoshells - Altbir-Drullinsky, D (Elsevier B.V., 2019)
Curvature of nanomagnets can be used to induce chiral textures in the magnetization field. Here we perform analytical calculations and micromagnetic simulations aiming to analyze the stability of in-surface magnetization configurations in toroidal nanomagnets. We have obtained that despite toroidal vortex-like configurations are highly stable in magnetic nanotori, the interplay between geometry and magnetic properties promotes the competition between effective interactions yielding the development of a core in a vortex state when the aspect ratio between internal and external radii of nanoturus is ≥0.75. © 2019 Elsevier B.V.